Implementation of Medical and Non-Medical Risk Management Infertility and Gynecology Over Kamala Clinics - Yudwi Erisha; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Ratna Indrawati Lestariani (Journal of Multidisciplinary Academic, 2021)
KAMALA Clinic is the main clinic which is a network of private clinics that provide fertility and gynecology special health services. KAMALA is under PT. Medika Sehat Utama and have committed to developing fertility and gynaecology clinics as well as offering an In Vitro Fertilization (IVF) program with a guarantee (self-insurance). However, the operation in this clinic requires risk management to protect the clinic from a significant level of risk which is hinder the achievement of Kamala's clinical vision. In achieving optimal service to patients, this clinic carries out of risk identification, risk analysis, and risk evaluation. In order to prevent and minimize the impact of risks on every part of the clinic, the risk management is used on ISO 31000 in 2018. The stages of the ISO 31000 in 2018 process, include communication and consultation, setting context, risk assessment consisting of risk identification, risk analysis and risk evaluation, risk mitigation, monitoring and review as well as recording and reporting. Meanwhile, the risk criteria used in the risk assessment are low, moderate, high and extreme/catastrophic risk. Each risk is managed by the risk owner by conducting a risk register, then assessing the likelihood of risk occurring and assessing the risk impact based on risk criteria. the results of the risk management assessment are carried out as supporting material in decision making in mitigating the impact of risks that occur so that management can improve the effectiveness of risk management implementation.